Teacher Strategy in Online Teaching and Learning: A Case Study in a Private Junior High School at Bantul - Patrisius Anggri Prassetyo; Yuyun Yulia (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2022)
The objective of this research is to describe teacher strategies in online teaching and learning and the problems found in online learning activities. This study employs a descriptive qualitative research design using data from teacher practices in online teaching and learning. The data was gathered through interviews and online class observations with the teacher at a private junior high school. The strategies reveal the teacher used, such as using video, practicing dialogue, discussing the material learning, the model of teaching with media utilized, providing feedback on the material lesson, collecting assignments, and motivating students to participate in online learning activities. Regarding problems, the issues were about students lack of participation. They did not listen to the explanations in online learning, they played with their phones, they did not do tasks or activities, and they did not activate the camera. They turned on the camera merely at the beginning and the end of online learning.